VALUE DIMENSION OF HIGH TECHNOLOGIES IN THE INFORMATION AGE - Ченбай, Н. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article focuses on the axiological aspects of high technologies in their relation to social and cultural factors